Recent advances in the pharmacotherapy of epilepsy: brivaracetam and perampanel as broad-spectrum antiseizure drugs for the treatment of epilepsies and status epilepticus. (22nd September 2019) - Willems, Laurent Maximilian; Bauer, Sebastian; Rosenow, Felix; Strzelczyk, Adam
ABSTRACT: Introduction : Antiseizure drugs (ASDs) play a central and crucial role in the treatment of epilepsy patients, as the majority require anticonvulsant treatment for an extended period of time. Since up to 30% of patients are refractory to medical treatment, new therapeutic options are necessary. Perampanel (PER) and brivaracetam (BRV) are the latest approved ASDs that may be considered in a variety of epilepsy syndromes. PER has a distinct and selective mode of action on α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and is licensed for use in focal and generalized epilepsies. BRV is a derivative of levetiracetam but exhibits a 20-fold higher affinity and a faster brain entry time as a synaptic vesicle glycoprotein 2A (SV2A) ligand. Areas covered : This article reviews the advances in the epileptic treatment and provides a comparison of PER and BRV. Both drugs have shown comparable results in randomized controlled trials, and both are well tolerated. Expert opinion : PER and BRV have the potential to perform as important, broad-spectrum ASDs with significant market shares. BRV's intravenous formulation and fast penetration into the brain and PER's unique mode of action will result in the more frequent use of both drugs in status epilepticus.